The Implementation Of Teaching Speaking On Explanation Using Live Presentation And Recorded Presentation On Whatsapp Application At Sma Muhammadiyah 9 Surabaya - Siti Imalia Tanjung; Linda Mayasari; Sofi Yuniati; Ramizah Rizqiya (PROCEEDING UMSURABAYA, 2019)
This research is conducted to apply teaching speaking by using live presentation and recorded presentation via WhatsApp application. The research design is descriptive qualitative, the researcher analyzed the eleventh grade of science program in senior high school of Muhammadiyah 9 Surabaya. The purpose of the research is to describe the implementation of teaching speaking on explanation text material by using live presentation and recorded presentation through WhatsApp, the students’ responses, the strength and weakness of this implementation. The result was the students could practice speaking English on WhatsApp application as the learning media with two different strategy; recorded presentation and live presentation. The responses of the students were very interest with the media that applied during teaching-learning process. The strength of recorded presentation was students can present better, meanwhile on live presentation, teachers can monitor directly if they have errors. However live and recorded presentation have the weakness. The weakness of recorded presentation was students cannot be monitored directly by the teacher and the weakness of live presentation was the learning time that was less efficient so that it required additional time. Keyword: Teaching speaking, Recorded Presentation, Live Presentation and Explanation Text